2023
DOI: 10.3390/ijms241411814
|View full text |Cite
|
Sign up to set email alerts
|

Chimerism Testing by Next Generation Sequencing for Detection of Engraftment and Early Disease Relapse in Allogeneic Hematopoietic Cell Transplantation and an Overview of NGS Chimerism Studies

Abstract: Chimerism monitoring after allogenic Hematopoietic Cell Transplantation (allo-HCT) is critical to determine how well donor cells have engrafted and to detect relapse for early therapeutic intervention. The aim of this study was to establish and detect mixed chimerism and minimal residual disease using Next Generation Sequencing (NGS) testing for the evaluation of engraftment and the detection of early relapse after allo-HCT. Our secondary aim was to compare the data with the existing laboratory method based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…It is essential to note that artificial samples cannot fully substitute for the clinical post-HCT samples from patients. Liacini et al [ 2 ] calculated the overall CV as 5.08% (ranging from 0% to 11.21% at the expected chimerism value of 0.1–10%), and Janakiraman et al [ 13 ] demonstrated within- and across-run variability of 4.7% and 4.1%, respectively. Additionally, Picard et al documented a lower LOQ (0.22%) than that reported by the manufacturer ( Table 5 ) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is essential to note that artificial samples cannot fully substitute for the clinical post-HCT samples from patients. Liacini et al [ 2 ] calculated the overall CV as 5.08% (ranging from 0% to 11.21% at the expected chimerism value of 0.1–10%), and Janakiraman et al [ 13 ] demonstrated within- and across-run variability of 4.7% and 4.1%, respectively. Additionally, Picard et al documented a lower LOQ (0.22%) than that reported by the manufacturer ( Table 5 ) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional benefits of AlloSeq HCT include its automated and user-friendly chimerism calculations [ 2 ]. The presented results encompass the percentage of DNA from each genetic contributor, QC status with reasons, the number of informative markers, and average marker coverage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations